Histopathological Analysis of Gastric Biopsies using Updated Sydney System - Muhammad Zubair; Nabeel Khan Afridi; Muhammad Amir Nawaid; Hassan Tariq; Akhter Ali Bajwa; Naveed Khan (Pakistan Armed Forces Medical Journal, 2022)
Objective: To analyse histopathological findings in gastric biopsies of patients with dyspepsia using an updated Sydney System.